Accelerate Self-Catabolism of Adipose Tissue: A Promising Way for Weight Loss - Yamin, Inés von (Science Insights, 2025)
Obesity is a multifaceted global health concern associated with numerous chronic diseases, including cardiovascular conditions, type 2 diabetes, and certain cancers. Traditional weight loss strategies—such as caloric restriction, exercise, and pharmacotherapy—have yielded inconsistent results for many individuals. A promising alternative lies in the body’s own capability to mobilize and catabolize adipose tissue. This hypothesis article explores the concept of accelerating self-catabolism of adipose tissue as a targeted and efficient method for sustainable weight loss. Drawing from advances in metabolic physiology, hormonal signaling, mitochondrial function, and gene expression, the paper posits that enhancing lipolytic pathways, modulating adipokines, and leveraging brown adipose tissue (BAT) thermogenesis could synergistically increase energy expenditure while reducing fat mass. I hypothesized that integrated interventions, including selective pharmacologic agents, thermogenic stimulation, and intermittent fasting, to activate endogenous fat-burning mechanisms. Ultimately, this approach may redefine obesity treatment paradigms by transforming fat tissue from a passive energy store into an active agent of weight loss.